A game-theoretic approach for power pricing in a resilient supply chain considering a dual channel biorefining structure and the hybrid power plant. (October 2022) - Rajabzadeh, Hamed; Babazadeh, Reza
Abstract: This study investigates power pricing decisions in a resilient supply chain, including the main biomass supplier, biorefinery, the hybrid power plant, and the backup supplier. The power plant's main fuel is considered biofuel derived from Jatropha Curcas L. (JCL). However, due to unavoidable uncertainties in biofuel supply links, the shortage in meeting demand is inevitable. Therefore, for increasing the supply chain's resiliency, the fossil fuel backup supplier is taken into account to make up the shortage with anticipated fossil fuel. Due to environmental concerns, the penalty cost is considered for excessive use of fossil fuel. The model is studied under two cases by considering a dual-channel biorefining. Different game-theoretic models are established for varied power configurations and interactions of supply chain members. It is observed from the numerical study that, depending on the fractional part of the power plant's requirements of biofuel and JCL supplied by the biorefinery (Case 1) and the main supplier (Case 2), respectively the performance of the supply chain increases in the presence of the backup supplier. Additionally, the sensitivity analysis shows that Case 1 is more profitable than Case 2 for chain members. Moreover, in contrast to the fossil fuel replacement coefficient, the greater the convertibility degree of the JCL, the larger the profits for the members. Highlights: Studying the power pricing decisions in a resilient supply chain. Considering backup supplier for a hybrid biofuel-fossil fuel power plant. Applying game-theoretic model for choosing the best supply chain structure. Conducting numerical study and performing sensitivity analysis.